PERANCANGAN SISTEM INFORMASI PENDAFTARAN ADMINISTRASI KEPENDUDUKAN MENGGUNKAN PHP DAN MYSQL DI KECAMATAN BUAHBATU KOTA BANDUNG - Denis Indirwan; Maman (INFOKOM (Informatika & Komputer), 2019)
This research was to know about the registration information system of population administration at Kecamatan Buahbatu Bandung City. The data colletion method used were observation, interview, and literature study which had relation with the main problems.The research was found about the running registration information system of pupolation administration was still simple and was done manually. New information system was made using PHP (hypertext Prepocessor) and Mysql as the database where it had purpose to simplify and help the process better than before, while the design method is using software development Waterfall with system design tool such as UML (Unified Modeling Language) tool.The suggestion that can be given that: (1) do the treatment start from computer device, scheduled the maintenance software & system information to maintain the performance (2) sustainable development at system information to keep the performance can improve & optimum.